Performance Measurement and Performance Management in OECD Health Systems - Hurst, Jeremy (OECD Labour Market and Social Policy Occasional Papers, 2001)
Health systems in OECD countries are under pressure to improve their performance. Against that background, this paper has three main aims: To compare concepts of the 'performance' of health care systems developed by the WHO and by the OECD, with 'performance frameworks' adopted in selected OECD countries. To compare the key indicators of performance derived from these proposed performance concepts. A secondary objective, here, is to try to identify new performance variables that might eventually be included in OECD Health Data. To compare and contrast the different performance management arrangements in the selected OECD countries, and to evaluate the extent to which there is evidence that new indicators and new institutions have been brought together successfully to improve performance itself. In order to achieve these aims, the paper reviews the performance frameworks and some of the performance indicators adopted recently by WHO, OECD, Australia, Canada, the UK and ...